Defect introduced paramagnetism and weak localization in two-dimensional metal VSe2. (26th October 2017) - Cao, Qiang; Yun, Frank F; Sang, Lina; Xiang, Feixiang; Liu, Guolei; Wang, Xiaolin
Abstract: We have carried out a detailed investigation of the magnetism, valence state, and magnetotransport in VSe2 bulk single crystals, as well as in laminates obtained by mechanical exfoliation. In sharp contrast to the ferromagnetic behavior reported previously, here, no ferromagnetism could be detected for VSe2 single crystal and laminate from room temperature down to 2 K. Neither did we find the Curie paramagnetism expected due to the 3 d 1 odd-electronic configuration of covalent V 4+ ions. Rather, intrinsic VSe2 is a non-magnetic alloy without local moment. Only a weak paramagnetic contribution introduced by defects is noticeable below 50 K. A weak localization effect due to defects was also observed in VSe2 single crystals for the first time.